Research site selection for SI-FMS initiative at Basona Worena woreda - Mengistu, Dejene Kassahun; Ebrahim, Mohammed; Tilahun, Mulugeta; Nigir, Bogale; Zeleke, Muluken; Alene, Temesgen (2022)
Ethiopia is among the five implementors of this initiative and the implementing team composed of individuals from various CG centres based in Addis Ababa, Ethiopia has made visited to the agreed project sites in Ethiopia on 30 August 2022. In north Shewa, it was agreed that Basona Worena will be the implementing site of this initiative activities. On this day, SI – MFS initiative implementing team composed of researchers from Alliance of Bioversity International and CIAT, ICARDA and ILRI has travelled to Debre Birhan area to select research site for integrated research efforts and technology aggregations. The objective of the site selection was to implement research interventions and improve the land, crop, and livestock productivity through sustainable intensification of the mixed farming system (SI-FMS) initiative. The team has discussed with Basona Worena Woreda of Agriculture and livestock offices to identify the specific project implementation kebele. After the purpose of the initiative was discussed site selection criteria was set to select the implementation kebele.